BUREAUCRATIC REFORM THROUGH ORGANIZATIONAL RIGHTSIZING - Denny Iswanto (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2024)
The essence of bureaucratic reform is the demand for very fundamental changes to the government bureaucratic structure which has so far been seen as having many internal problems within it. Bureaucratic reform aims to build organizations that are agile and oriented towards public services with a focus on improving bureaucratic institutions. Bureaucratic reform by all regional apparatus including the Regional Planning, Research and Development Agency (BAPPELITBANGDA) of Pasuruan Regency indicates that regional apparatus are obliged to prepare organizational institutions appropriately, both in terms of size, main tasks, and functions and also appropriate for use. One of the Pasuruan Regency government's efforts in institutional reform is to change the nomenclature of Regency Regional Apparatus from BAPPELITBANGDA to Regional Research and Innovation Agency (BAPPERIDA). The type of research used by researchers is descriptive research with a qualitative approach. The data sources used are secondary data and the data analysis techniques used are interactive analysis techniques. The research results show that BAPPELITBANGDA Pasuruan Regency has combined elements of planning, research, and development by following the latest nomenclature. This change impacts the main tasks and functions of BAPPELITBANGDA which does not focus on development planning alone. Still, research and development is one of its main tasks and functions, even though research and development is not yet running optimally. With changes in size and function in the context of rightsizing, it can provide a more appropriate bureaucratic structure, so that the Rightsizing Organization structure can have the right function and size so that it can improve organizational performance. Keywords: Bureaucratic Reform; Rightsizing; Nomenclature Change.